Assessment of the association between the presence of fragmented QRS and the predicted risk score of sudden cardiac death at 5 years in patients with hypertrophic cardiomyopathy - Ozyilmaz, Sinem; ÇETİN, MUSTAFA; Akgul, Ozgur; Uyarel, Huseyin; Pusuroglu, Hamdi; Karayakali, Muammer; Gul, Mehmet; Satilmisoglu, Hulusi; Yildirim, Aydin; Bakir, Ihsan (My University, 2017)
Objective: It has been shown that the presence of fragmented QRS (fQRS) is associated with poor prognosis in many cardiovascular diseases and in patients with hypertrophic cardiomyopathy (HCM). However, no study has shown an association with the absolute risk score of sudden cardiac death. The aim of this study was to determine the relationship between QRS and the predicted risk score of sudden cardiac death at 5 years (HCM Risk-SCD) in HCM patients.